OCCURRENCE OF FIVE HOLOTRICHIA SPECIES (COLEOPTERA: SCARABAEIDAE: MELOLONTHINAE) IN MAHARASHTRA AND THEIR MALE GENITALIA CHARACTERIZATION - S. M. DADMAL; S. S. KHADAKKAR; P. A. GHUGE (The Bioscan, 2013)
In Maharashtra, Holotrichia Hope is one of the most economically important genus of Coleoptera: Scarabaeidae: Melolonthinae, attacking Soybean, Sugarcane, Sorghum, Groundnut and many other field crops. The specimens were collected from five different agro-climatic zones of Maharashtra viz, South Konkan, Western ghat hills, Northern hills, Western Vidarbha plains and Eastern Vidarbha hills during 2012-2013. Male genitalia characterization has got prime importance as a species diagnostics tool. Thus, the investigations were carried out and described accordingly on external morphological characters and male genitalia. Studies revealed the presence of five species viz. Holotrichia serrata (Fabricius), Holotrichia fissa Brenske, Holotrichia akolana Khan and Ghai, Holotrichia reynaudi (Blanchard) and Holotrichia nagpurensis Khan and Ghai. Morphologically they were slightly varied. However, in male genitalia, significant variations were noticed in parameres, phallobase, endophallus and spiculum gastrale. Holotrichia serrata (Fabricius), was found to be the most prevalent species in every agro-climatic zones of Maharashtra.